Evaluation of the National Control of Diarrhoeal Disease Programme in the Philippines, 1980-93 - Baltazar Jane C.; Nadera Dinah P.; Victora Cesar G. (The World Health Organization, 2002)
OBJECTIVE: To evaluate the impact of the National Control of Diarrhoeal Disease Programme (NCDDP) in the Philippines over the period 1980-93, describing levels and trends in programme activities, and relating them to severe diarrhoea morbidity and mortality among under-5-year-olds. METHODS: Routinely collected data on morbidity and mortality trends were obtained from health statistics reports of the Health Intelligence Service and the NCDDP. Socioeconomic indicators, including annual average family income and expenditures, gross national product, and unemployment rates, were derived from the Philippine population census data collected by the National Statistics Office. FINDINGS: In relation to baseline levels, diarrhoea mortality among infants and young children fell by about 5% annually over the 18-year period under review. The decline was faster than those related to acute respiratory infections (ARIs) among children of similar age and to perinatal causes. Diarrhoea hospital admission rates registered an annual decline of 2.4% relative to the baseline level. CONCLUSION:These findings suggest that the programme had a substantial impact; the period under review also witnessed some degree of improvement in other factors with positive influences on health, such as exclusive breastfeeding, nutrition and environmental sanitation. The quality, particularly completeness and reliability, of the existing data did not allow further analysis, thus, making it difficult to conclude beyond doubt that the observed trends indicate that they were solely due to NCDDP.